A. J. Montoya, Historia de los saladeros argentinos, Buenos Aires, Editorial Raigal (Col. Campo Argentino), 1956, 107 p. - M. Z. (1957)
Fil: M. Z.. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras